Association of hyperleptinemia with peripheral arterial disease in hypertensive patients - I-Ching Huang; Chao-Chien Chang; Bang-Gee Hsu; Chung-Jen Lee; Ji-Hung Wang (Tzu-Chi Medical Journal, 2017)
Objective: Hypertension is a risk factor for peripheral artery disease (PAD). Serum leptin plays an important role in promoting endothelial dysfunction. The aim of this study is to investigate whether the leptin level is associated with PAD in hypertensive patients. Materials and Methods: Ninety-eight hypertensive patients were enrolled in this study. Ankle-brachial index (ABI) values were measured using an automated oscillometric device. Patients with an ABI value <0.9 were considered the low ABI group. C-reactive protein (CRP) was measured using standard enzymatic automated methods. Serum levels of human leptin were determined using a commercially available enzyme immunoassay. Results: Eighteen (18.4%) hypertensive patients were included in the low ABI group. Hypertensive patients in the low ABI group had higher serum creatinine (P < 0.001), CRP (P = 0.003), and leptin (P < 0.001) levels, higher prevalence of diabetes (P = 0.036), and current smoking (P = 0.034) than patients in the normal ABI group. Univariate linear regression analyses revealed that body weight (P = 0.014), waist circumference (P = 0.010), body mass index (P = 0.002), and logarithmically transformed CRP (log-CRP,P= 0.001) were positively correlated with serum log-leptin levels in hypertensive patients. Multivariate stepwise linear regression analysis showed that log-leptin (β = 0.439, adjusted R2 change = 0.224,P< 0.001) was also an associated factor of PAD in hypertensive patients. Conclusion: A higher log-leptin value is an independent predictor of PAD in hypertensive patients.